1995
DOI: 10.1177/0265407595123002
|View full text |Cite
|
Sign up to set email alerts
|

Social Structural and Psychological Correlates of Interethnic Dating

Abstract: This study is designed to: (a) describe current interethnic dating behavior and related attitudes among southern Californians; and (b) examine social structural and psychological correlates of interethnic dating. Data were derived from a telephone survey conducted with a probability sample of African American, Latino and white residents of southern California. lnterethnic dating was reported by over half of all ethnic groups and both sexes and more frequently among men. Most reported that family members knew o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
49
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 15 publications
5
49
0
Order By: Relevance
“…This is in line with the more recent study by Tucker and Mitchell-Kernan (1995) in California who found that among Blacks, Whites and Latinos, men had more often than women engaged in interethnic dating. The stronger opposition against interethnic dating found in the present sample among males may reflect the fact that, when answering the questions, males had especially in mind men from other ethnic groups who were dating women from their own ethnic group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in line with the more recent study by Tucker and Mitchell-Kernan (1995) in California who found that among Blacks, Whites and Latinos, men had more often than women engaged in interethnic dating. The stronger opposition against interethnic dating found in the present sample among males may reflect the fact that, when answering the questions, males had especially in mind men from other ethnic groups who were dating women from their own ethnic group.…”
Section: Discussionsupporting
confidence: 91%
“…Men tend to have generally more prejudices towards outgroup members than women (e.g., Pratto, Sidanius, & Levin, 2006), which might be accompanied by more negative attitudes towards intergroup marriages. However, it is difficult to make an unequivocal prediction on gender differences in the attitude towards dating members of other ethnic groups.For example, a study by Tucker and Mitchell-Kernan (1995) in California found that Black, White and Latino men had considerably more often than women from these groups engaged in interethnic dating (see also Feliciano, Robnett, & Komaie, 2009 …”
mentioning
confidence: 99%
“…Being African American and a first generation college student likely provides added pressure to succeed in an academic setting. Finally, worth noting is the notion that marriage rates have steadily declined among African Americans (BoydFranklin, 2003;Tucker & Mitchell-Kernan, 1995). Along these lines, many African American students may come from single parent homes where academic success may have added meaning not only to the individual, but also for the individual's immediate family.…”
Section: Discussionmentioning
confidence: 99%
“…While seemingly a positive image of Asian Americans, the model minority image carries a particular raced and gendered taint, that for Asian American men, manifests as both emasculating and desexualizing (J.W. Chan, 1998; J.P. Chan, et al , 1991 ;Cheung, 1993;Tucker & Mitchell-Kernan, 1995). Thus, for Asian American men to fully understand themselves and the challenges they must overcome, it is important for Asian American men to understand themselves simultaneously as raced, classed, and gendered individuals (Ting, 1998).…”
mentioning
confidence: 99%